The Miguelist counter-revolution and the liberal political exile: Portugal and Brazil (1828-1834) - Gonçalves, Andréa Lisly; Martins da Silva, Luiz Gustavo (Almanack, 2024)
This article discusses some aspects of the process of political emigration resulting from the dynamics between revolution and counterrevolution in Portugal in the 1820s and 1830s. Although the direction of the exiles varied according to the outcome of the successive disputes that took place in the country between royalists and liberals, it was when D. Miguel came to power in 1828 that an estimated ten thousand people, accused of being fierce liberals, were forced to leave the country. Seeking to emphasize the transnational and transcontinental nature of this migratory phenomenon, we point out the conditions in which these emigrants found themselves, as well as the different destinations they took, including, among them, Rio de Janeiro and other provinces of Brazil.